Students Resilience: The Impact of Online Learning Policies During The Covid-19 Pandemic on Academic Stress - Oktaviani Puspita Sari; Nani Mediatati (Universitas Negeri Semarang, 2023)
The focus of this research is to investigate the symptoms of academic stress, its causes, and its impact on student resilience during the Covid-19 pandemic's online learning policies. This research used a qualitative approach conducted in April-June 2021 at two state vocational high schools in Salatiga, Central Java, Indonesia through an online survey and interviews. The results show that many students were experiencing symptoms of academic stress when online learning policies during the Covid-19 pandemic such as sleep disturbances, difficulty concentrating, irritability, headaches, and even physical illness due to overwhelming stress levels. The highest indicator that caused academic stress came from pressure to complete all subject's test targets and assignments in a limited time, disruption to the teaching and learning system, limited access to the internet network, preparation for graduation, and the difficulties students experienced in understanding the subject matter. Strong support networks, along with competent self-management, excellent social relationships, emotional control, and integration, can have a significant impact on student resilience. Overall, especially strong self-management has a very large influence in preventing or overcoming academic stress problems. Support networks are very important in limiting the impact of academic stress on student resilience during the Covid-19 pandemic online learning policies.